An Analysis of Road Crash Black Spots on the East-West Highway in Kanchanpur District, Nepal - Khadka, Rabin; Negi, Crimsan Singh; Pali, Puja; Giri, Laxmi; Badal, Dinesh; Bhandari, Kumar; Mahara, Rajesh (International Journal on Engineering Technology and Infrastructure Development, 2025)
Road traffic crashes remain a pressing public safety concern, particularly along high-traffic corridors such as the East-West Highway in Kanchanpur, Nepal. This study seeks to identify and analyze accident-prone zones commonly referred to as “black spots” along this critical highway segment, with the goal of proposing actionable measures to reduce crash incidence and severity. To systematically assess high-risk areas, secondary crash data spanning multiple fiscal years were obtained from the Traffic Office. The Weighted Severity Index (WSI) was employed to quantify and rank the severity of crashes, enabling the preliminary identification of black spots. Further validation was conducted through field studies, where the Prioritization Index (PI) was calculated to refine risk assessments and prioritize intervention zones. The findings highlight distinct variations in risk levels along the highway, with Gulariya and Kaluwapur emerging as the most hazardous sections, while Bangaun and Suda exhibited comparatively lower crash risks. Major contributing factors included sub-optimal road design, insufficient signage, reckless driving behaviors, and weak enforcement of traffic regulations. In response to these findings, the study proposes targeted mitigation strategies, such as infrastructure upgrades, improved road signage, enhanced traffic law enforcement, and periodic safety audits. Addressing these challenges will enable authorities to enhance traffic safety and minimize the socio-economic impact of road crashes in the region. The study advances road safety discussions by delivering evidence-based recommendations suited to Nepal’s EastWest Highway. Future research could explore real-time traffic analysis and long-term evaluations of the proposed interventions.